Pengaruh Konten YouTube WOW (Wellspring Of Wellness) Hungary Terhadap Minat Berkunjung Mahasiswa - Defanya Daniella Ester Sompie; Mariam Sondakh; Leviane Jackelin H. Lotulung (Universitas Mercu Buana, 2022)
This research aims to know The Influence of WOW (Wellspring Of Wellness) Hungary’s YouTube Content Towards Visiting Interest of Students at Communication Science Faculty of Social and Political Science Sam Ratulangi University. The theory used in this research is stimulus-organism-response or s-o-r theory. Research method used in this research is quantitative with data retrieval technique of using questionnaires. The population of this research were 33 Students of Communication Science Faculty of Social and Political Science Sam Ratulangi University who also subscribed to channel Visit Hungary. The result showed that there are 42,1 percent influence between WOW Hungary’s YouTube content towards visiting interest. The most influential out of 5 indicators are Video, Audio and Title, in which many respondes answered with agree and strongly agree, whereas the least influential is Comment. In hypothesis testing, the significant value obtained was 0,000 so Ha was accepted and Ho rejected because the significant value is smaller than 0,05. In conclusion WOW Hungary’s YouTube content has an effect towards the visiting interest of Communication Science students Faculty of Social and Political Science Sam Ratulangi University Manado.